The western Roman embassy to the court of Attila in A.D. 449 - Gračanin, Hrvoje (Array, 2003)
The author analyzes the data about the Western Roman embassy to Attila's court in AD 449 which are presented by Priscus of Panium in his fragmentary preserved historical work. The aim of the paper is to propose a plausible hypothesis about true purpose of the embassy by linking it with the Iusta Grata Honoria affair. The paper also deals with the encounters between two imperial embassies since the Western Roman embassy coincided with the Eastern Roman one, discusses the information about the Western Roman envoys, and summarizes Priscus' account on the voyage and stay of the Eastern Roman envoys at Attila's court.